Konseling anak-anak : Sebuah pengantar praktis / Kathryn Geldard; David Geldard ; pengalih bahasa, Gianto Widijanto, Lilian Yuwono, penyunting, Tim Indeks - GELDARD, Kathryn; Geldard David; Gianto Widijanto; Lilian Yuwono; Tim Indeks (Indeks, 2012)
vii, 397 hlm. : ilus. ; 25 cm (3 eks.)